1987
DOI: 10.1111/j.1432-1033.1987.tb10991.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ribosomal peptidyltransferase by chloramphenicol. Kinetic studies

Abstract: The mechanism of action of chloramphenicol in inhibiting peptide bond formation has been examined with the aim of discovering whether chloramphenicol brings about conformational changes in the peptidyltransferase domain, its target locus on the ribosome. These conformational changes have been sought as changes in the catalytic rate constant of peptidyltransferase. A detailed kinetic analysis of the inhibition of the puromycin reaction in a system derived from Escherichia coli [Kalpaxis et al. (1986) Eur. J. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
8

Year Published

1997
1997
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 33 publications
0
29
0
8
Order By: Relevance
“…The mechanism by which chloramphenicol and p-aminosalicylate inhibit the Mg-chelatase activity is not clear. Chloramphenicol binds to ribosomes and interferes with the peptidyl transferase activity (Drainas et al 1987). p-Aminosalicylate in millimolar concentrations is known to disrupt protein RNA interactions (Parish and Kirby 1966).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism by which chloramphenicol and p-aminosalicylate inhibit the Mg-chelatase activity is not clear. Chloramphenicol binds to ribosomes and interferes with the peptidyl transferase activity (Drainas et al 1987). p-Aminosalicylate in millimolar concentrations is known to disrupt protein RNA interactions (Parish and Kirby 1966).…”
Section: Discussionmentioning
confidence: 99%
“…2C). Chloramphenicol in micromolar concentrations is known to inhibit protein synthesis (Drainas et al 1987).…”
Section: Barley Mg-chelatasementioning
confidence: 99%
“…The action of the aminoglycosides is presumably targeted against more than one single cellular process [9]. From the literature, Chl prevents the peptidyltransferase reaction [10]; Ery is believed to act by blocking the translocation of peptidyl-tRNA from the A to the P site [11]; Fus inhibits the same step by binding to Elongation factor G [12], and Tet prevents binding of aminoacyl-tRNA mainly to the A site [13]. Finally, Pur is an aminoacyl-adenosine analog and leads to premature chain termination [11].…”
Section: Introductionmentioning
confidence: 99%
“…Crystallographic studies showed that chloramphenicol binds either to the hydrophobic crevice to the entrance of the peptide exit tunnel of Haloarcula marismortui [39], or to the active site hydrophobic crevice of Deinococcus radiodurans ribosomal subunits [40], suggesting that both of these sites may be physiologically relevant. It was suggested that these two different chloramphenicol binding sites observed in the structural studies of the archaeal (H. marismortui) and eubacterial (D. radiodurans) 50S subunits most likely correspond to the two binding sites on eubacterial 50S subunits that have been inferred previously from binding [41] and kinetic studies [42,43].…”
Section: Effect Of Small Rna Ligands On Ribosomementioning
confidence: 94%